Electronic warfare pocket guide - Adamy, David L. (SciTech Publishing, 2011)
This book discusses EW definitions and subareas; antennas; radio propagation; receiver sensitivity; communication jamming; communications electronic protection; jamming LPI communications; radar characteristics; radar electronic protection; expendable countermeasures; decoys; decibels; graph and nomograph instructions; list of symbols in formulas and list of abbreviations.